The Emergence of Separatist Transnistria - Wróbel, Jacek (Institute of National Remembrance Review, 2025)
Transnistria is a separatist state entity located in a territory internationally recognised as part of the Republic of Moldova, on the left bank of the Dniester River. Its creation resulted from factors both internal – including the concerns of the Transnistrian population over Romanian nationalism in an independent Moldova and the efforts of local elites to maintain control over the region – and external, namely the Kremlin’s strategy of leveraging Transnistrian separatism to retain influence over Moldova. This article analyses the causes of Transnistrian separatism, reconstructs the process of its emergence and continued existence of an unrecognised de facto state, and outlines the political, economic, and international context of the region, as well as the peace process.